THE FORMATION OF UZBEKISTAN CLASSICAL LITERATURE AND EASTERN CLASSICAL GENRES IN MODERN UZBEKISTAN POETRY (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes the process of formation of Uzbek classical literature and the continuity and transformation of oriental classical genres in modern Uzbek poetry. The study used historical-comparative, formal-stylistic, intertextual and sociocultural methods. The results show that while Uzbek classical literature enriched genres such as ghazal, masnavi, rubai, and qasida with a national spirit, modern poetry reinterprets these genres with new content, free verse and modernist styles. Also, modern poets are inspired by classical genres and use them as a means of expressing national independence, human values and modern social problems. The article identifies the place of classical heritage in modern literature and makes scientific proposals regarding its creative prospects.